MONITORING LINES AND TUBES ON CHEST RADIOGRAPH IN THE CARDIAC INTENSIVE CARE UNIT - Muhammad Jamil Akhtar; Muhammad Hamid Saeed; Qaiser Mahmood et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT: A variety of medical devices are used in the intensive care unit for long durations. Each one of them is a double-edged sword: intended to save life, but life-threatening if in the wrong place. Hence, it is important to periodically check that these devices are correctly placed so as to prevent complications. The portable chest radiograph is of tremendous value in this context. OBJECTIVE: Following the completion of this exercise the individual should be able to recognize the common complications of mechanical lines and their correct positioning as well as normal and pathological appearances of portable chest x-rays in cardiac intensive care unit.